Pengembangan Bahan Ajar IPA Tema 8 Menggunakan Model Project Based Learning Di Sekolah Dasar - Suang Kupon Syukur; Yanti - Fitria; Farida F (PendIPA Journal of Science Education, 2022)
This research is motivated by teaching materials that do not do project learning. This research aims to describe the development process and produce thematic integrated teaching materials on theme 8 using a valid, practical, and effective Project Based Learning (PPA) model for fifth grade elementary school students. This type of research is research and development. The development model carried out is a 4-D model. This research was conducted at SDN 39 Mata Air. The research subjects were students of class V. The validity of the research data was obtained using the RPP validation questionnaire sheet and teaching materials. Practicality data were collected through the lesson plan implementation observation sheet, teacher and student questionnaire responses. The effectiveness is taken from the activities, and student learning outcomes. Based on the validity test, data was obtained that the lesson plans and teaching materials from expert validators and category validators were very valid. The practicality test results from the implementation of lesson plans, teacher responsibility costs and student assessment are very practical categories. The results of the effectiveness test on the results of activities with the active category and learning outcomes obtained a proportion of the results from the KKM. Based on these results, it can show that integrated thematic teaching materials using the Project Based Learning (PPA) model for grade V SD students are valid, practical, and effective.